PENERAPAN MEDIA DIGITAL CANVA UNTUK MENINGKATKAN PARTISIPASI PESERTA DIDIK DALAM PEMBELAJARAN IPA DI KELAS IV SDN 02 KINALI - Hanifah; Elfia Sukma; Inggria Kharisma (STKIP Subang, 2026)
The development of digital technology offers significant opportunities to improve the quality of learning in elementary schools. One digital medium that teachers can utilize is Canva, an easy-to-use graphic design application for creating engaging and interactive learning materials. This article discusses the application of Canva-based digital media to increase student participation in science learning in fourth-grade students at SDN 02 Kinali. The methods used included interactive presentation media, educational posters, and simple learning videos created using Canva. The results showed increased student participation in learning activities, such as active participation in asking questions, answering questions, discussing topics, and completing group assignments. Furthermore, the use of Canva created a more engaging and enjoyable learning environment, thus increasing student motivation in science learning.